Analisis Kecerdasan Majemuk dan Karakter Mahasiswa FIP Universitas Negeri Medan Berdasarkan Pendekatan Statistik Deskriptif - Septiani, Ayu; Utami, Tri Puspita Nur; Athika, Azza; Salsa, Natjwa; Situmorang, Lenarti; Sirait, Hillary Hecylia Br (CV. Eracita Grup, 2025)
Higher education plays an important role in developing students’ potential holistically, encompassing both intelligence and character. One relevant approach to understanding this diversity is the theory of multiple intelligences, which views intelligence as a set of varied abilities. This study aims to analyze and describe the profiles of multiple intelligences and character among students of the Faculty of Education, Universitas Negeri Medan (UNIMED), using a descriptive statistical approach. A quantitative descriptive method with total sampling was applied to 25 students from several study programs. The research instruments included the Multiple Intelligences Score (MIS) and a character assessment instrument, with data collected online through Google Forms. Data were analyzed using descriptive statistics in the form of frequencies and percentages. The results indicate dominant intelligences in naturalistic, verbal/linguistic, musical, visual/spatial, kinesthetic, and interpersonal areas, along with prominent character traits such as resilience, communication ethics, responsibility, perseverance, honesty, and cooperation. These findings suggest that students of the Faculty of Education at UNIMED possess strong intelligence and character profiles relevant to the demands of education and the professional world.